VVVX survey dusts off a new intermediate-age star cluster in the Milky Way disk - Garro, Elisa (2024)
Context. In the last decade, many new star clusters have been discovered in heavily obscured regions of the Milky Way bulge and disk. Aims. Our primary long-term objective is to seek out additional star clusters in the poorly studied regions of the Milky Way, where detections pose significant challenges. The aim of this pursuit is to finalize the Milky Way’s globular and open cluster system census and to gain a comprehensive understanding of both the formation and evolution of these systems and our Galaxy as a whole. Methods. We report the discovery of a new star cluster, named Garro 03. We investigated this new target using a combination of near-infrared and optical databases. We employed the VISTA Variables in the Via Láctea Survey and Two Micron All Sky Survey data in the near-infrared, and the Gaia Data Release 3 and the DECam Plane Survey datasets in the optical passband. We constructed density maps and vector proper motion diagrams in order to highlight our target. We performed a photometrical analysis in order to derive its main physical parameters. Results. Garro 03 is located at equatorial coordinates RA = 14:01:29.3 and Dec = −65:30:57.0. From our photometric analysis we find that this cluster is not heavily affected by extinction with AKs = 0.25 ± 0.04 mag and AG = 1.54 ± 0.02 mag. It is located at heliocentric distance of 14.1 ± 0.5 kpc, which places Garro 03 at 10.6 kpc from the Galactic centre and Z = −0.89 kpc below the Galactic plane. We also calculated the mean cluster proper motion of (μα*,μδ)=(−4.57 ± 0.29, −1.36 ± 0.27) mas yr−1. We derived an age of 3 Gyr and metallicity [Fe/H] = −0.5 ± 0.2 by the isochrone-fitting method, employing the PARSEC models. The total luminosity was derived in the Ks and V bands, finding MKs = −6.32 ± 1.10 mag and MV = −4.06 mag. Finally, the core and tidal radii were measured constructing the Garro 03 radial density profile and fitting the King model. We obtained rc = 3.07 ± 0.98 pc and rt = 19.36 ± 15.96 pc, respectively. Conclusions. We photometrically confirm the cluster nature for Garro 03, located in the Galactic disk. It is a distant, low-luminosity, metal-rich star cluster of intermediate age. We also searched for possible signatures (streams or bridges) between Garro 03 and Garro 01, but we exclude a companionship with the present analysis. We need spectroscopic data to classify it as an old open cluster or a young globular cluster, and to understand its origin.